PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DI KOTA PEKANBARU (STUDI KASUS DI KELURAHAN SRI MERANTI KECAMATAN RUMBAI) - Desvita Nindya Wulandari; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Family Expectation Program is Conditional Cash Transfer program to accelerate poverty alleviation and development of the social security system provided to RTSM/KSM in an effort to improve human resources especially in education and health. Implementation of The Family Expectation Program in Pekanbaru began in 2013 to include 8 sub-districts, one of it is Rumbai. According to directly observation, the problem is implementation of The Family Expectation Program in Rumbai Sub-district is not optimal, especially in Sri Meranti Village. The purpose of this research is to knowing how the implementation of The Family Expectation Program in Sri Meranti Village Rumbai Sub-district and to knowing the obstacle factor implementation of The Family Expectation Program in Sri Meranti Village Sub-district Rumbai.The theory used is management by George R. Terry starting from planning, organizing, actuating and controlling. This research uses a qualitative descriptive method. In collecting the data researcher uses the method of observation, interview and documentation.The result of this research gets conclution that implementation of The Family Expectation Program in Pekanbaru is not optimal. There is still a shortage especially in planning and organizing implementation of The Family Expectation Program. And then, the obstacle factor in implementation of The Family Expectation Program in Pekanbaru (the case studies in Sri Meranti Village Rumbai Sub-district), that is socialization, budgetting, completness requirement and lack of awareness RTSM/KSM.Keywords: The Family Expectation Program, Health, Education, Poverty